The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4314/tjpr.v13i12.25
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Biological Activities of <i>Zanthoxylum limonella</i> (Rutaceae): A Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 36 publications
(28 reference statements)
1
38
0
2
Order By: Relevance
“…The results from this study showed that essential oils from both species had broad spectrum antibacterial activity to Gram positive and negative bacteria. This is in accordance with other studies that showed broad spectrum antibacterial activity from these oils (Naik et al, 2015;Supabphol and Tangjitjareonkun, 2014;Tangjitjareonkun et al, 2012a). In this study, Z. rhetsa essential oil showed similar MIC/MBC level against all tested bacteria at 256/256 mg/mL while the essential oil from Z. limonella showed greater antibacterial activity with variable MIC/MBC levels ranging from 4-128/8-128.…”
Section: Discussionsupporting
confidence: 92%
“…The results from this study showed that essential oils from both species had broad spectrum antibacterial activity to Gram positive and negative bacteria. This is in accordance with other studies that showed broad spectrum antibacterial activity from these oils (Naik et al, 2015;Supabphol and Tangjitjareonkun, 2014;Tangjitjareonkun et al, 2012a). In this study, Z. rhetsa essential oil showed similar MIC/MBC level against all tested bacteria at 256/256 mg/mL while the essential oil from Z. limonella showed greater antibacterial activity with variable MIC/MBC levels ranging from 4-128/8-128.…”
Section: Discussionsupporting
confidence: 92%
“…[4][5][6][7][8][9][10] Limonene, terpinen-4-ol, sabinene, 3-carene, α-terpineol, β-pinene, α-pinene, γ-terpinene, α-terpinene, pcymene and linalool are the most common molecules found in the genus. [4][5][6][7][8][9][10] Limonene, terpinen-4-ol, sabinene, 3-carene, α-terpineol, β-pinene, α-pinene, γ-terpinene, α-terpinene, pcymene and linalool are the most common molecules found in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…[4 -10] As is well-known, several investigations have demonstrated anticarcinogenic and antitumor activity of plant essential oils. [4][5][6][7] Considering this fact, we focused on evaluating the essential oils from Z. limoncello on the human decarboxylase enzyme (ODC1), which is considered as a promising target for controlling several types of cancer. [7] The antitumor and antiproliferative activities of organic extracts and chemical fractions belonging to the genus Zanthoxylum has been explored, however, no insights regarding the bioactive compounds from these plants on specific physiological targets have been revealed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations